IMPACT OF NUTRITION EDUCATION ON JUNK FOOD CHOICES AMONG TEENAGERS - Mishra, Sadhana; Singh, Kiran (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Background: Adolescence is a critical stage of growth and development during which adequate nutrition supports physical health, growth, immunity and long-term disease prevention. Unhealthy dietary practices, frequent junk-food and fast-food consumption, physical inactivity and sedentary lifestyle patterns may contribute to overweight, obesity, gastric problems and other diet-related health risks. Fast food is commonly preferred by teenagers because of taste, convenience, attractive presentation and easy availability; however, many fast-food items are high in calories, fat, salt and sugar and have comparatively low nutritional value. Objective: The present study aimed to assess the impact of nutrition education on junk-food and fast-food choices among adolescents. The study also examined nutrition awareness, food preferences, body mass index status and changes in healthy food choices after counselling. Methods: The study was conducted among 100 adolescents selected from schools of ATS, Gadarpur, Udham Singh Nagar, Uttarakhand. A structured questionnaire was used to collect information on fast-food choices, eating habits, frequency of fast-food consumption, nutrition education awareness and preference for healthy foods. Anthropometric measurements were recorded to assess nutritional status using body mass index. Nutrition education and counselling were provided to adolescents and their mothers through interactive guidance, pamphlets, healthy recipe booklets and diet-related educational materials. Data were summarized using frequencies and percentages and presented through tables and figures. Results: Before counselling, pizza was the most commonly preferred fast food (43%), followed by burgers (27%), Chinese food (14%) and sandwiches (13%). Only 3% of adolescents reported healthy food choices, and no adolescents reported fruits and vegetables as a preferred choice before counselling. BMI assessment showed that 30% of adolescents were overweight and 35% were obese, while 24% were in the normal BMI category and 11% were underweight. After counselling, preferences for fast-food items decreased, whereas healthy food choices increased. Pizza preference reduced from 43% to 25%, burger preference from 27% to 12%, Chinese food from 14% to 9% and sandwich preference from 13% to 5%. In contrast, healthy food choices increased from 3% to 27%, and fruits and vegetables increased from 0% to 22%. Conclusion: The findings indicate that nutrition education and counselling can positively influence dietary awareness and food choices among adolescents. School-based nutrition education, counselling of mothers, nutrition pamphlets and healthy recipe booklets may help adolescents reduce frequent fast-food consumption and adopt healthier dietary practices.